I need it as fast as possible
If the problem were to factor g(x) = –15x^6 + 5x^4 + 3x^2:
g(x) = –15x^6 + 6x^4 + 3x^2
g(x) = –3x^2(5x^4 – 2x^2 – 1)
h(x) = 5x^4 – 2x^2 – 1
h(x) = 5(x^2)^2 – 2(x^2) – 1
x^2 = (- -2 ± √(4-4(-5)) )/(2*5)
x^2 = (2 ± 2√(1+5) )/(2*5)
x^2 = (1 ± √(6) )/5
x = ± √( (1 ± √(6) )/5 )
g(x) = –3x^2(x ± √( (1 ± √(6) )/5 ) )
g(x) =
–3x^2
* (x – √( (1 + √(6) )/5 ) )
* (x + √( (1 + √(6) )/5 ) )
* (x – √( (1 – √(6) )/5 ) )
* (x + √( (1 – √(6) )/5 ) )
g(x) = –15x^6 + 6x^4 + 3x^2
g(x) = –3x^2(5x^4 – 2x^2 – 1)
h(x) = 5x^4 – 2x^2 – 1
h(x) = 5(x^2)^2 – 2(x^2) – 1
x^2 = (- -2 ± √(4-4(-5)) )/(2*5)
x^2 = (2 ± 2√(1+5) )/(2*5)
x^2 = (1 ± √(6) )/5
x = ± √( (1 ± √(6) )/5 )
g(x) = –3x^2(x ± √( (1 ± √(6) )/5 ) )
g(x) =
–3x^2
* (x – √( (1 + √(6) )/5 ) )
* (x + √( (1 + √(6) )/5 ) )
* (x – √( (1 – √(6) )/5 ) )
* (x + √( (1 – √(6) )/5 ) )
Comments